Upadacitinib for the treatment of psoriatic arthritis - Diogo Fonseca; Miguel Nogueira; Tiago Torres (BioExcel Publishing Ltd, 2023)
Psoriatic arthritis is a chronic systemic inflammatory disease that presents with a variable clinical course and is typically associated with joint inflammation, together with cutaneous psoriasis. In recent decades, knowledge of the pathogenesis of psoriatic arthritis has advanced considerably and has allowed for development of new highly effective therapies, transforming the treatment landscape. Upadacitinib is a Janus kinase inhibitor (JAK) that is orally reversible with high selectivity for JAK1 and its signal transduction molecules. The results obtained in the phase III clinical trials (SELECT-PsA 1 and SELEC-PsA 2) demonstrated that upadacitinib was highly effective over placebo and non-inferior to adalimumab in several important domains of the disease. Improvements were observed in dactylitis, enthesitis and spondylitis as well as in physical function, pain, fatigue and overall quality of life. The safety profile of these results resembled that of adalimumab, apart from a slightly higher rate of herpes zoster infection, an increase of creatine kinase and an incidence of lymphopenia. However, none of these events was considered a serious adverse advent. Additionally, another analysis demonstrated that combining upadacitinib with methotrexate was associated with a similar efficacy to upadacitinib in monotherapy, both for patients that are naive to biologics treatment and for those previously treated with biologics. Therefore, upadacitinib is a new option for the treatment of psoriatic arthritis, presenting a series of beneficial characteristics. At this stage, it is important to collect long-term data to confirm the efficacy and safety profiles shown in clinical trials.